A systematic literature review of economic evaluations of pneumococcal conjugate vaccines in east and southeast Asia (2006-2019). (3rd July 2022) - Wang, Bruce Cm; Chaiyakunapruk, Nathorn; Zhu, Shuiqing; Babigumira, Joseph B.; Furnback, Wesley; Chitale, Ramaa; Gamil, Amgad; Zhao, Kun; Wasserman, Matt
ABSTRACT: Introduction: Pneumococcal infections can lead to serious invasive diseases such as meningitis, septicemia and pneumonia, as well as milder but more common illnesses such as sinusitis and otitis media. The World Health Organization (WHO) recommends the inclusion of pneumococcal conjugate vaccines (PCVs) in infant National Immunization Program (NIP) programs worldwide. Decision-makers in Asian countries planning to introduce PCVs in their respective NIP will need a comprehensive evidence of effectiveness of PCVs at the population level and economic evidence including cost-effectiveness. Areas Covered: A systematic literature review (from 1/1/2016 to 10/11/2019) of PCVs in East and Southeast Asia to understand (1) the contributing factors to cost-effectiveness results of PCVs and (2) whether gaps in evidence exist suggesting why the region may have yet to implement full NIPs. Expert Opinion: In East and Southeast Asia, vaccination with PCVs was found to significantly reduce the mortality and morbidity of pneumococcal diseases and was cost-effective compared to no vaccination. Study assumptions, specifically vaccine local acquisition, the inclusion or exclusion of indirect effects (serotype replacement and herd effect), cross-protection, and protection against nontypeable haemophilus influenzae and serotype 3, were the main drivers of cost-effectiveness.